Dairy effluent management systems as a potential persistence source of Shiga toxin-producing Escherichia coli (STEC) strains - Basualdo, Jessica (2024)
Shiga toxin-producing Escherichia coli (STEC) is a group of pathogenic enterobacteria of significant public health importance due to their association with highly prevalent human diseases. STEC is ubiquitous in livestock environments, and its presence in the environment emphasizes the importance of properly managing agricultural effluents to reduce health risks from contamination. In order to detect STEC in the effluent treatment systems of two dairy farms (“A” and “B”) in the southwest of Buenos Aires province, samples (“A”, n = 88; “B”, n = 72) were taken at two different times of the year (winter and spring) and at various points in the treatment systems. Analysis markers for virulence genes (stx, eae, saa, and ehxA) revealed the presence of STEC in 13.1% of the samples, showing an increase in spring and differences between dairy farms possibly related to their maintenance conditions. After manure, sediments showed the highest proportion of STEC-positive samples, which is relevant due to the ability of these strains to survive in the environment through biofilm formation. Eight genetic profiles were identified among all STEC-positive samples, which are associated with STEC strains that can cause hemolytic uremic syndrome (HUS) and other gastrointestinal diseases. This demonstrates the role of dairy farm environments in the region as reservoirs of pathogenic STEC strains and their impact on public health.